Tajemnica bankowa a prywatność - przykład Szwajcarii i Anglii : [Bank secrecy and privacy – cases of Switzerland and England] (Studia Prawnicze / The Legal Studies, 2010)
Prawna regulacja tajemnicy bankowej zmienia się wraz z mentalnością społeczności, w której obowiązuje. Obecnie wyraźnie zarysowuje się tendencja do „rozluźniania” obowiązku milczenia. Wciąż wzrasta liczba wyjątków od tego obowiązku, a jego naruszenie jest coraz częściej postrzegane jako niewykonanie lub nienależyte wykonanie umowy bankowej.W niniejszym opracowaniu podejmuję próbę wykazania, że stopień nasilenia wskazanego zjawiska zależy w znacznej mierze od tego, czy w danym porządku prawnym dostrzegany jest związek pomiędzy tajemnicą bankową a ochroną sfery prywatnej jednostki (jej autonomią informacyjną), jak również od wagi, jaką przywiązuje się do samej prywatności. Proces ograniczania obowiązku poufności jest nierozerwalnie związany z „kurczeniem” się sfery prywatnej. Uważam bowiem, że do sfery tej należy zaliczyć objęte tajemnicą bankową informacje dotyczące majątku jej beneficjentów. Poddaję więc analizie relacje pomiędzy powinnością milczenia a sferą prywatną jednostki na gruncie Europejskiej Konwencji o Ochronie Praw Człowieka i Podstawowych Wolności (dalej: EKPC lub Europejska Konwencja o Ochronie Praw Człowieka), Karty Praw Podstawowych Unii Europejskiej (dalej: Karta lub Karta Praw Podstawowych) oraz porządków prawnych państw, które przyjęły skrajnie odmienne rozwiązania prawne w analizowanym przeze mnie zakresie, tj. Szwajcarii i Anglii. Although banking secrecy has been rooted in the European legal culture for a long time, its legal regulations have constantly evolved together with the development of information technology, changes in social perception and the approach to privacy issues within the society. Recently, there has been a growing tendency to “soften” the banking secrecy obligation, multiply exceptions from this obligation and to perceive its breach as a non-performance or improper performance of a banking contract. The aim of this article is to examine the relation between banking secrecy and privacy. The author attempts to show that the level of protection afforded to banking secrecy depends on whether, in a given jurisdiction, a link is seen between the said secrecy and the protection of an individual’s privacy. In the article it is observed that the tendency to limit the scope of banking secrecy results from a greater limitation on personal privacy. Such observation is connected with the fact that the sphere of privacy encompasses information protected by banking secrecy. Accordingly, this article contains an analysis of relations between the banking secrecy obligation and the private sphere in the light of the European Convention of Human Rights and Fundamental Freedoms as well as the Charter of Fundamental Rights of the European Union under laws of Switzerland and England – which went in two opposite directions in the legal approach to the subject matter. The author looks at banking secrecy as an instrument of protecting individual’s privacy. The right to privacy is a fundamental human right and is protected by local and international legal measures. This entails the necessity to apply to banking secrecy not only the constitutional norms but also international standards of protection. It also requires that each exception from the confidentiality obligation be tested against the rule of proportionality and not be interpreted extensively. Switzerland, where the legal regulation of banking secrecy appears to be among the most restrictive ones in Europe, acknowledged that the right to privacy constitutes a source of the banking secrecy obligation, which was confirmed by the notable judgment of the Federal Tribunal of 1938. The example of Switzerland confirms that in jurisdictions where respect for personal rights is seen as a source of banking secrecy, the secrecy obligation is strict. In principle, in such jurisdictions the secrecy obligation is linked with delictual liability (which does not exclude a claim based on a contract), and its breach can be subject to criminal sanctions. On the other hand, England is an example of a jurisdiction where greater attention appears to be given to the public interest than to the individual’s, and where less attention is given to the link between disclosing confidential information and a breach of privacy. In this jurisdiction a tendency to attach contractual liability to the breach of secrecy can be observed. This is due to that fact that banking secrecy in England is treated as an implied contractual term between a bank and its client and results from a special relationship of trust between them. In consequence, liability for breaching the banking secrecy obligation is contractual in nature which can make it difficult or impossible for a banking secrecy beneficiary to obtain compensation for moral injury. In England, the scope of exceptions from banking secrecy obligations is less precise as compared to Switzerland and public authorities have easier access to confidential information.